2014
DOI: 10.1097/sla.0b013e3182a690ff
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategy for Main Duct Intraductal Papillary Mucinous Neoplasms of the Pancreas Based on the Assessment of Recurrence in the Remnant Pancreas After Resection

Abstract: One-step total pancreatectomy can be avoided, and remnant total pancreatectomy would lead to favorable outcomes even in patients with pancreatic recurrence, some cases of which seem to involve residual lesions. Postoperative surveillance of high-grade dysplasia should be performed as if malignant, and close attention should be paid to the occurrence of concomitant pancreatic ductal adenocarcinomas in patients with MD-IPMNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 31 publications
1
65
1
Order By: Relevance
“…At present, only invasive carcinoma derived from IPMN is considered malignant, and high-grade dysplasia is not considered malignant [4,6]. However, this has recently been questioned, as there have been some reported cases of high-grade dysplasia recurring as a distant metastasis after resection [8,9]. High-grade dysplasia is regarded as an indication for surgical resection as stated in the Fukuoka guidelines [4], although it is not clearly defined as malignant [6].…”
Section: Definitions and Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, only invasive carcinoma derived from IPMN is considered malignant, and high-grade dysplasia is not considered malignant [4,6]. However, this has recently been questioned, as there have been some reported cases of high-grade dysplasia recurring as a distant metastasis after resection [8,9]. High-grade dysplasia is regarded as an indication for surgical resection as stated in the Fukuoka guidelines [4], although it is not clearly defined as malignant [6].…”
Section: Definitions and Classificationmentioning
confidence: 99%
“…Ideno et al [67] investigated the histological subtype of IPMN in patients with concomitant pancreatic cancer, and found a high frequency of gastric subtype. Concomitant pancreatic cancer may occur in patients with MD-IPMN as well as BD-IPMN [8]. Furthermore, distinct pancreatic cancer may develop even after the resection of IPMN.…”
Section: Invasive Pancreatic Cancer Concomitant With Ipmnmentioning
confidence: 99%
“…Besides recurrence of invasive IPMN, several investigators have reported recurrent lesions after resection of noninvasive IPMN 39, 40, 41, 42, 43, 44. We also experienced peritoneal dissemination after resection of high‐grade IPMN 7. Even after resection of noninvasive IPMN, especially high‐grade IPMN, attention should be paid to the development of recurrent lesions.…”
Section: Surveillance After Resection Of Ipmnmentioning
confidence: 79%
“…IPMN comprises main duct type (MD‐IPMN), branch duct type (BD‐IPMN), and mixed type (MD + BD). MD‐IPMN more frequently progresses to malignant lesions (60‐70%)2, 5, 6, 7 than BD‐IPMN,2, 5, 8 although BD‐IPMN is more commonly seen than MD‐IPMN 9, 10. Researchers have also hypothesized that benign BD‐IPMN may develop distinct pancreatic ductal adenocarcinoma (PDAC) synchronously or metachronously.…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons often encounter difficulties in determining the extent of resection, in particular for patients with main duct-type IPMN, even when using intraoperative ultrasonography (IOUS) [17,18,19]. Furthermore, neoplasms with low malignant potential, such as IPMN, appear to present an adequate indication of laparoscopic surgery with navigation surgery technology because of the lack of tactile or three-dimensional (3D) sensation [4,20,21].…”
Section: Introductionmentioning
confidence: 99%